Pollen viability in a cultivated sunflower line, in the wild sunflower (Helianthus annuus L. ssp. texanus Heiser) and in its hybrid offspring - Mendoza Villarreal, Rosalinda; Reyes-Valdés, M. Humberto; Espinosa Zapata, Carlos; Villarreal Quintanilla, José Ángel (Instituto de Ecología, A.C., 2006)
To evaluate possible developmental alterations in male gametes in the progeny of a sunflower inter-subspecific cross, pollen viability was studied in the cultivated line AN-3, the wild subspecies Helianthus annuus ssp. texanus, and in the hybrid from the cross CMS-AN-3 x H. annuus ssp. texanus. Among the hybrid plants, 95% of the individuals showed male fertility, thus indicating that the target wild populations contain male-sterility restoration alleles. Pollen viability did not show significant differences between the hybrid (91.5%), the cultivated (94.6%) and wild parents (95.2%). Results suggest that pollen viability is a trait maintained at high levels in wild and cultivated sunflower populations, and that there is no indication that sunflower domestication had an effect on this character. Regarding the use of wild material to improve the cultivated sunflower, pollen viability is not a barrier to use local populations (southeast of Coahuila) of H. annuus ssp. texanus to introduce wild genetic material to elite varieties.